2021
DOI: 10.1039/d1ra00341k
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine based antimicrobial polymers: a review

Abstract: Mode of action of piperazine based polymers against pathogenic microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Piperazine is a common functional group in medicinal chemistry, prevalent in the structures of diverse small-molecule pharmaceuticals as well as in multiple psychoactive substances . Consequently, many studies involving liquid chromatography and tandem mass spectrometry have been carried out to identify signature MS/MS transitions for the detection and quantitation of these compounds. ,, Among these studies, frequently reported fragmentations involve cleavage at the bond connecting the piperazine with the rest of the molecule, formation of tetrahydropyrazinium product ions, loss of neutral piperazine or formation of piperazine radical cations .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piperazine is a common functional group in medicinal chemistry, prevalent in the structures of diverse small-molecule pharmaceuticals as well as in multiple psychoactive substances . Consequently, many studies involving liquid chromatography and tandem mass spectrometry have been carried out to identify signature MS/MS transitions for the detection and quantitation of these compounds. ,, Among these studies, frequently reported fragmentations involve cleavage at the bond connecting the piperazine with the rest of the molecule, formation of tetrahydropyrazinium product ions, loss of neutral piperazine or formation of piperazine radical cations .…”
Section: Resultsmentioning
confidence: 99%
“…Piperazine. Piperazine is a common functional group in medicinal chemistry, prevalent in the structures of diverse small-molecule pharmaceuticals 41 as well as in multiple psychoactive substances. 42 Consequently, many studies involving liquid chromatography and tandem mass spectrometry have been carried out to identify signature MS/MS transitions for the detection and quantitation of these compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The higher activity of PVA-E-Pz against E. coli may be due to the presence of thinner cell wall than S. aureus [64,65]. PVA-E-Pz's antibacterial properties is due to the presence of piperazine, which affects the cytoplasmic membrane of bacteria, allowing intercellular components to flow out and eventually causing cell lysis [56,66]. To compare the results, antimicrobial activity of ciprofloxacin (10 mg) was measured and it exhibited a zone of inhibition of 45 mm and 46 mm against S. aureus and E. coli, respectively.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…24 The prevalence of substituted piperazines shows the relevance of N -heterocycles in therapeutic development. 25,26 In the list of FDA-approved pharmaceuticals, piperazine is the third most prevalent saturated N -heterocycle. 27 On this point, we executed and optimized solvent-free mechanochemical procedures for obtaining a library of N -substituted amines under milder reaction conditions in a short reaction time with excellent yields without any further purification.…”
Section: Introductionmentioning
confidence: 99%